2021
DOI: 10.3390/su13073593
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Management of Online to Offline Delivery Apps for Consumers’ Reuse Intention: Focused on the Meituan Apps

Abstract: The COVID-19 pandemic has significantly changed our daily life, especially in the food industry. This study aims to examine the sustainable factors that influence the reuse intention in China’s online-to-offline (O2O) food delivery industry, using “Meituan Waimai” app users as the objects of investigation. Meituan had great success in the initial stage of business due to the rapid urbanization of the major Chinese cities, and thus it is planning to enter the second and third level of cities in China. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 21 publications
(27 reference statements)
1
31
0
Order By: Relevance
“…The literature review confirmed that several Sustainability 2021, 13, 12857 2 of 16 variables from the Theory of Planned Behavior (hereafter TPB) influence food purchase intention [12][13][14][15][16][17]. According to Ellison et al (2021) [18], there is an ongoing shift toward online food purchasing, while Choi et al (2021) [10] affirmed that more people are using food delivery apps. Several studies on such delivery apps have found that they can impact loyalty, service quality, packaging and customer satisfaction [19].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The literature review confirmed that several Sustainability 2021, 13, 12857 2 of 16 variables from the Theory of Planned Behavior (hereafter TPB) influence food purchase intention [12][13][14][15][16][17]. According to Ellison et al (2021) [18], there is an ongoing shift toward online food purchasing, while Choi et al (2021) [10] affirmed that more people are using food delivery apps. Several studies on such delivery apps have found that they can impact loyalty, service quality, packaging and customer satisfaction [19].…”
Section: Introductionmentioning
confidence: 80%
“…Against this background, the present research seeks to determine the factors that positively and significantly influence consumers' food purchasing during the COVID-19 pandemic under two situations: whether people (1) are eating at a fast-food restaurant and (2) are using a food delivery service via mobile apps. To this end, we followed several studies and emphasized purchase intention as an important factor [9][10][11]. The literature review confirmed that several Sustainability 2021, 13, 12857 2 of 16 variables from the Theory of Planned Behavior (hereafter TPB) influence food purchase intention [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…SERVQUAL has explained the service quality in the majority of O2O scenarios. Nevertheless, many similar constructs have been proposed to better understand consumer behavior, such as accuracy [16], efficiency [26], and interaction quality [72]. Delivery service quality is a unique service quality dimension in the O2O food delivery scenario.…”
Section: Service and Product Qualitymentioning
confidence: 99%
“…The compatibility adapted from the diffusion of innovations theory developed by Rogers [84] is another factor that determines consumers' technology use behavior, whose similar constructs are facilitating conditions and perceived behavior control [45,46]. Some researchers also discussed the technical attributes of O2O commerce from the perspective of system quality, such as system safety [16,32] and privacy protection [14]. These technical or utilitarian factors were mentioned in the reviewed articles and constructed into a theme, as shown in Figure 5.…”
Section: Technical and Utilitarian Factorsmentioning
confidence: 99%
See 1 more Smart Citation